Implementation Of Lesson Study As An Innovative Professional Development Model Among Mathematics Teachers - Chiew, Chin Mon (2009)
Kajian kualitatif ini meneroka perlaksanaan “Lesson Study” sebagai satu model perkembangan profesional guru Jepun